Análise e validação de escala da Síndrome de Burnout em guardas municipais : (uma pauta para aposentadoria especial?) - Cicognani Júnior, Wilson Klippel (2021)
The present research was carried out in a sample of 1,717 Municipal Guards from a universe of 2,391 from all regions of the country (more than 1% of all national staff) with the application of a scale for the Burnout Syndrome - MBI, a questionnaire to assess aggressive behavior, a socio-demographic questionnaire and data on possible psychic treatment. It is a quantitative research using the SPSS and Qualtrics platform and a qualitative research with bibliographic review and comparison of national and foreign literature. The search was sent by an electronic link to the Municipal Guard, without any personal contact between researcher and researched. The problem was established in clarifying the attributions of the Municipal Guard as a typical police activity, and if it would be subject to the same stressors of the other policemen, including Burnout, and if as a result, it would be using its actions more aggressively. A historical digression was made about the attributions of the Municipal Guards, their current attributions, and a bibliographic review about the Burnout Syndrome and other stressors, in addition to a comparison with dozens of researches extracted from CAPES (Plataforma Sucupira) and the LILACS platform, making a thorough analysis of other 21 researches on this topic. Among all the researches, there were still many conclusive discrepancies regarding the measurement of Burnout Syndrome. It was found that there is still much doubt about the real attributions of the Municipal Guard in the practical field. Many municipalities act as if they were military policemen, and others exercise their legal role that runs through preventive policing. Of any luckily they are subjected to very high emotional tensions that involve extreme emotional exacerbation. A clarification had been made on all the international literature on the theme of Burnout Syndrome, as a new disease whose pathology presents itself in three dimensions, emotional exhaustion, depersonalization and professional achievement. A new validation of the MBI scale was performed to be used in Municipal Guards that obtained satisfactory results through the SPSS platform. The same procedure was used for the aggressive behavior questionnaire by the SPSS, showing coherence indices for its applicability. The results did not indicate the incidence of Burnout Syndrome in view of the professional achievement index, therefore the discussion on the incidence fell into possible measurement errors in the SPSS commonality table. Regarding aggressiveness, possible aggressive tendencies resulting from emotional exhaustion and depersonalization were seen as predictive factors. The final conclusions are due to the need for greater attention to the mental health and working conditions of the Municipal Guards, and improvements in their career, especially the special retirement due to the very high emotional stress factors that were measured in this research.